Results of endovascular correction of atrial septal defect and early heart remodeling in children of preschool and school age - R. S. Tarasov; P. A. Shushpannikov; V. I. Ganyukov; I. N. Sizova (Российский кардиологический журнал)
Aim. To analyze the results and features of early cardiac remodeling (CR) in children of preschool and school age after endovascular correction of atrial septal defect (ASD).Material and methods. A prospective study included 27 children with secondary ASD who underwent endovascular correction for one year (from the beginning of 2017 to the beginning of 2018). The patients were divided into two groups. The first (n=12) — children of preschool age (<8 years old), mean age 4,5 [3;6], and the second (n=15) — school age (818 years old), mean age 12 [9;14]. The following indicants were assessed during hospitalization: the success of the intervention, hospital complications, functional data characterizing CR according to echocardiography before and after the correction of the defect.Results. It was shown that all children successfully completed endovascular closure of ASD. Complications were not identified. We find several statistically significant changes in echocardiogram data before and after the intervention. In the preschool age group, the size of the right ventricle (RV) decreased from 1,66 to 1,45 cm (p=0,028), the right atrium (RA) decreased from 3,58 to 3,1 cm (p=0,003), and the longitudinal size of RV decreased from 3 to 2 cm (p=0,032) and basal size of RV — from 5,98 to 4,4 cm (p=0,005), the volume of RA decreased from 25,7 to 20,7 ml (p=0,005). In the group of school age, the size of the RV changed from 2,08 to 1,8 cm (p=0,038), the size of the RA — from 3,72 to 2,71 cm (p=0,007), the RV area in diastole — from 12,4 to 10,6 mm2. The gradient has changed from 2 to 1,54 mm Hg (p=0,043), the frontal size of the tricuspid valve (TV) decreased from 2,7 to 2,48 cm (p=0,010). The basal size of RV decreased from 3 to 2,6 cm (p=0,015), the median size — from 2,73 to 2,37 cm (p=0,017) and the longitudinal size — from 5,97 to 5,45 cm (p=0,007). No significant differences in CR among the groups were found.Conclusion. We made conclusion about the efficacy and safety of endovascular correction of ASD, which has a positive effect on early HR in children, both in early and in old age.